Evaluating the Integration of Sustainability Concepts in Plant Design Projects within the Chemical Engineering Programme at Universiti Malaysia Sabah - Chu, Chi-Ming; Nurhazwani Yusof Azudin; Rachel F. Mansa; Sivakumar Kumaresan (Penerbit UMS, 2025)
This paper presents a brief evaluation of the Capstone Chemical Engineering Design Courses, Plant Design Project I & II, offered in the fourth and final year of undergraduate study at Universiti Malaysia Sabah. One main focus is to identify the elements of sustainability as concepts delivered in the courses to align with United Nations’ Sustainability Goals and the latest Engineering Accreditation Standard (2024). Though the concept of sustainability is not explicitly measured, it is found to be substantially linked to the criteria for selecting alternative designs and optimisation of the final design in the project. Strengths and weaknesses of the courses are discussed, with reference to five institutions’ concepts and pedagogy on sustainability, along with recommendations for improvements in the courses in the near future. According to a study by one of the institutions, the subject of process control requires particular attention when designing a plant, as it is highlighted by professional engineers as pivotal in optimising plant operation for sustainability.